Tennyson and Goethe's faust - Baynes, Tom (Edinburgh University Press, 2021)
Shows that Faust was a central influence on Tennyson's creative life.
Keywords: Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Criticism and interpretation.; Goethe, Johann Wolfgang von, -- 1749-1832 -- Influence.; Goethe, Johann Wolfgang von, -- 1749-1832. -- Faust. -- English.; Goethe, Johann Wolfgang von, -- 1749-1832; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892; Faust (Goethe, Johann Wolfgang von); English.; Germanic & Scandinavian languages.; C 1800 to c 1900.; Poetry by individual poets.; Indo-European languages.; Modern period, c 1500 onwards.; Poetry.; Languages.; Time period.; Literature & literary studies.; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Influence (Literary, artistic, etc.); Criticism, interpretation, etc.